Assessing the Impact of Health Service Providers and Recipients on the Adoption of E-health Services - MohammadTaghi Taghavifard; Akbar Yousefvand (مجله انفورماتیک سلامت و زیست پزشکی, 2020)
Introduction: By increasing the age of population, time considerations, the cost of health care services and the increase in unnecessary referrals to service centers, dissatisfaction among both health care providers and health service recipients are observed. By providing electronic services, part of this dissatisfaction will be eliminated. This requires the acceptance of e-health services. Given the cost of investment in this area for service providers, achieving the desired results is very important. Considering the limitations of the previous research works including  the lack of comprehensive studies, reliance on self-declaration and lack of paying attention to both the provider and recipient of services, investigation of factors which has the greatest impact on the acceptance of these services and removes some of the constraints of previous studies is of great significance. Method: This research was an applied-descriptive one. The statistical sample of this study included information technology experts and physicians. The measurement tool was a qualitative type based on interviews and questionnaires. The data were collected and analyzed using Delphi-Fuzzy method. Results: The values of defuzzified variables showed that the average values of all indexes were greater than 0.5, therefore, all indicators were confirmed. The research findings show that health care providers and recipients are both effective in using e-health services. Conclusion: Based on the findings of this study, it is suggested that managers and designers provide e-health services with taking into account the needs and preferences of both parties